Malaysia's New Economic Policy in Its First Decade : The Role of the State in Economic Developement, 1971-1980 - Toh, Kin Woon (Malaysian studies series, 2024)
Based upon Toh Kin Woon’s 1982 Doctoral thesis – now published for the first time – Malaysia’s New Economic Policy in Its First Decade offers an account of Malaysia’s renowned economic programme in the first decade of its development. Written by an engaged scholar, this book chronicles the genesis and controversies that surrounded the early years of the New Economic Policy, whilst offering an interpretation of the NEP informed by the progressive political economy of the period. Focussing upon issues of employment restructuring, the restructuring of ownership and control, and approaches to poverty eradication, Malaysia’s New Economic Policy in Its First Decade argues that what underlay the NEP was a particular relationship between class and the state, centred on the rise of a Malay bureaucratic capitalist class. This in turn limited the ability of the NEP to realise a more meaningful restructuring of Malaysian society. In the years after Toh Kin Woon’s thesis the politics of Mahathirism and subsequent development policies – from the National Development Policy onwards – would slowly alter the earlier vision of the NEP. Yet Malaysia’s New Economic Policy in Its First Decade offers us an opportunity to return to the complex debates of the time, and calls for us to move beyond a narrative about the NEP centred on race, to emphasise the important relationship between class and the state.